Effect of Political Factors on the Performance of Specialized Journalists in Iraqi Electronic Journalism - Mohammed, Ahmed Hatem; Al-Sammer, Abdulsalam Ahmed (ALBAHITH ALALAMI, 2023)
This study aimed to identify the political factors influencing the performance of specialized journalists in Iraqi electronic newspapers. The significance of the study stems from the role of communication in newspapers that have established themselves in reality due to their wide dissemination, multiple uses, expanding freedom base, and the current diversity in perspectives. These newspapers highlight and publish societal issues of concern. The importance of these newspapers is associated with their creators who face various factors affecting their value and performance, whether positively or negatively. In light of this, the political factor was identified as the primary driver for other influencing factors. The researcher employed a survey method to address the study’s questions and objectives, targeting specialized journalists working in Iraqi electronic newspapers, amounting to 128 individuals from 27/9/2022 to 27/10/2023. The study took into account personal variables of the participants such as gender, age, and educational attainment. Several findings emerged from the study, including that 75% of males versus 25% of females work as specialized journalists. Moreover, personal inclination was found to be the strongest motivator for journalists, and there are notable impacts of political factors on the communicative competence of the specialized journalist.